Institutional entrepreneurship in constructing alternative paths: A comparison of biotech hybrids - Lori Divito de Paauw (The University of Manchester, Manchester Business School, 2009)
This paper investigates how firms adapt their innovation strategies to cope with constraints in national institutional environments. It is a comparative case study of Dutch and British dedicated biotechnology firms focusing on a particular type of strategy, the hybrid model. Patterns of skill accumulation and learning present in the Dutch hybrids are indications of how they use institutional advantages to focus on low-risk innovation and build deeper competences while also pursuing high-risk innovation strategies. The Dutch hybrid offers insight into how firms comply with the dominant logic of the biotechnology field even when their institutional frameworks encourage the pursuit of low-risk innovation strategies.
Keywords: 330; biotechnology; national business systems; national innovation systems; varieties of capitalism; institutional entrepreneurship; Innovationspolitik; Institutionalismus; Unternehmer; Rationales Verhalten; Biotechnische Industrie; Systemvergleich; Niederlande; Großbritannien